Two new species of Rigidoporus (Agaricomycetes) from Brazil and new records from the Brazilian Amazonia - Gomes-Silva, Allyne Christina; de Medeiros, Priscila Sanjuan; Soares, Adriene Mayra Da Silva; Sotão, Helen Maria Pontes; Ryvarden, Leif; Gibertoni, Tatiana Baptista (Phytotaxa, 2014)
Two new polypores, Rigidoporus grandisporus and R. mariae are described from the Brazilian Amazonia based on specimens deposited in herbarium INPA between 27 and 39 years ago, and material recently collected in the State of Par￡. Besides the description of the new species, R. crocatus and R. undatus are reported as new records from the Brazilian Amazonia. Rigidoporus amazonicus, R. lineatus, R. ulmarius and R. vinctus are new records to different states of the Brazilian Amazonia. A key to the Rigidoporus species known for the Neotropics is provided.